2013
DOI: 10.3390/ijms14036487
|View full text |Cite
|
Sign up to set email alerts
|

RUFY, Rab and Rap Family Proteins Involved in a Regulation of Cell Polarity and Membrane Trafficking

Abstract: Cell survival, homeostasis and cell polarity rely on the control of membrane trafficking pathways. The RUN domain (comprised of the RPIP8, UNC-14, and NESCA proteins) has been suggested to be implicated in small GTPase-mediated membrane trafficking and cell polarity. Accumulating evidence supports the hypothesis that the RUN domain-containing proteins might be responsible for an interaction with a filamentous network linked to actin cytoskeleton and/or microtubules. In addition, several downstream molecules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…It is critical for these multidirectional transports to be adequately modulated, and abnormity at any point of membrane transport network could result in diseases [4]. Rab GTPases, which belong to the Ras superfamily of small GTPbinding proteins, are important mediators for membrane transport of both lipid and protein in human cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is critical for these multidirectional transports to be adequately modulated, and abnormity at any point of membrane transport network could result in diseases [4]. Rab GTPases, which belong to the Ras superfamily of small GTPbinding proteins, are important mediators for membrane transport of both lipid and protein in human cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…11 These processes, in turn, mediate the normal membrane polarity. [12][13][14] Besides, these Rab GTPases can be activated by distinct types of Rab GEFs and down-regulated by Rab GAPs. 15 Rab10, a member of the Rab family, is an important participant in formation of endoplasmic reticulum, secretion of basement membrane and translocation of glucose transporter type 4.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins share several common biochemical properties; for example, their activated (GTP-bound) form is selectively bound to specific adapter proteins for signal trans-duction (1). A group of such adapter proteins was recently shown to contain a RUN domain which is involved in binding small G proteins (2) of which one, RUN and FYVE domaincontaining 3 (Rufy3; 2 also known as Singar1/Rap2-interacting protein X), lacks an FYVE domain, which interacts with phosphatidylinositol 4,5-bisphosphate, and therefore cannot directly associate with the cell membrane (2). The analysis of Rufy3 using X-ray crystallography has shown that Rap2, a Ras family member, is tightly and stably bound to Rufy3 in a GTPand RUN domain-dependent manner (3).…”
mentioning
confidence: 99%